Cr(VI) Removal by Recombinant Escherichia coli Harboring the Main Functional Genes of Sporosarcina saromensis M52 - An, Qiuying; Zhang, Min; Guo, Dongbei; Wang, Guangshun; Xu, Hao; Fan, Chun; Li, Jiayao; Zhang, Wei; Li, Yi; Chen, Xiaoxuan; You, Wanting; Zhao, Ran (Frontiers in Microbiology, 2022)
Hexavalent chromium [Cr(VI)], a recognized heavy metal pollutant, has attracted much attention because of its negative impact on the ecological environment and human health. A chromium-resistant strain, Sporosarcina saromensis M52, was discovered, and the functional genes orf2987, orf3015, orf0415 and orf3237 were identified in the strain by genomics. With the advancement of DNA recombination and gene-splicing technology, genetic engineering technology was used to produce recombinant strains 2987, 3015, 0415 and 3237. The study revealed Cr(VI) tolerance in the order of M52 ≈ 2987 > 3015 ≈ 0415 > 3237 and reduction abilities in the order of M52 ≈ 2987 > 3015 > 0415 ≈ 3237. SEM-EDS, XRD, FT-IR and XPS were utilized to examine the surface structure of the recombinant strains and analyze the surface components and main functional groups. A comprehensive review of the recombinant strains' capacity to tolerate and reduce Cr(VI) revealed that orf2987 and orf0415 were the main functional genes in Sporosarcina saromensis M52, which may play a key role in removing Cr(VI) and protecting the strain, respectively. The optimum pH for recombinant strains 2987 and 0415 was 7.5-8.5, and the optimum temperature was 37 °C. Cu2+ had the greatest promotional effect when Cr(VI) was removed by them, while SDS had an inhibitory effect. This research provided the foundation for further study into the mechanism of Cr(VI) reduction in Sporosarcina saromensis M52, as well as a theoretical basis for the development of effective engineered strains to repair Cr(VI) contamination.